Condition And Monitoring Temperature Berbasis Mikrokontroler Pada Motor Produksi Di PT. Indah Kiat Pulp And Paper Perawang - Rahman, Ridho; Amri, Rahyul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
For maintaning stabilitation of production machines in PT. Indah Kiat Pulp and Paper Perawang, it monitores everyday. Monitoring which is done one of about the temperature. It aims to avoid the damages in production machines because of over temperature. In temperature monitoring, the method is done by companies still based on manually with used thermo mini tool. Monitoring with used thermo mini tool need many times because there are many production machines. Beside that, that all are done in one month, thus the data is not real time. Because of that the writer designed condition and monitoring tool based on microcontroller with used temperature sensor LM35. Microcontroller arduino uno used wireless communication, it used RF 433 Mhz and graphic display used LabView software. The aims to give the real time data, quick and easy in monitoring.The result of the research which had been done stated that the condition and monitoring based on microcontroller in production machines in PT. Indah Kiat Pulp and Paper Perawang had been applied successfull. Percentage error ratio sensor LM35 based on microcontroller with thermo mini tool based on manually 1.02%. Speed of time in taking the data reach 5 second with effective interval connectivity RF 433 Mhz as far as 5 meter.Keywords : LM35 sensor, Arduino Uno, RF 433 Mhz, LabView.